2023
DOI: 10.1039/d2nr06107d
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron radiation circular dichroism spectroscopy reveals that gold and silver nanoparticles modify the secondary structure of a lung surfactant protein B analogue

Abstract: Synchrotron radiation circular dichroism shows that gold and silver nanoparticles modify the secondary structure of lung surfactant protein-B analogue SP-B1–25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…It is effective in the case of studying protein interactions with nanoparticles. Our colleagues have shown [ 33 ] that the size and concentration of nanoparticles affect the peptide conformation, in particular, reducing the number of α-helices and increasing the number of β-sheets. In our study, at pH 3.9 and 7.5, on the contrary, there is an increase in α-helices and a decrease in the number of β-sheets.…”
Section: Discussionmentioning
confidence: 99%
“…It is effective in the case of studying protein interactions with nanoparticles. Our colleagues have shown [ 33 ] that the size and concentration of nanoparticles affect the peptide conformation, in particular, reducing the number of α-helices and increasing the number of β-sheets. In our study, at pH 3.9 and 7.5, on the contrary, there is an increase in α-helices and a decrease in the number of β-sheets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SRCD was used to demonstrated that Au and Ag nanoparticles can cause conformational changes in the structure of a key component of surfactant protein B, which plays a key role in the biophysical function of lung surfactant and is essential to life, which could change its effect in vivo, potentially leading to alterations in lung surfactant function and ultimately the physiological behavior of the lung [70]. In this case, most of the spectral change occurs bellow 210 nm.…”
Section: Synchrotron Radiation Circular Dichroism (Srcd) Spectroscopymentioning
confidence: 99%
“…The formation of PCs is a complex process that is influenced by the properties of the protein (protein charge, hydrophobicity, size, conformation) and by the properties of the nanomaterial (nanoparticle size, shape, functionalization) . Numerous advances in experimental techniques have led to a better understanding of the influence of some of these factors on PC formation. Among the characterization techniques employed, some rely on changes in size and surface charge during the formation of the PC including dynamic light scattering (DLS), fluorescence correlation spectroscopy (FCS), UV–visible spectroscopy, , and gel electrophoresis. , In addition, mass spectrometry (MS), , circular dichroism (CD), , and Fourier transform infrared spectroscopy (FT-IR) , enabled the identification and quantification of proteins in the corona. However, as most techniques are not in situ, they result in long processing times, molecular biases in purification processes, and loss of single-particle information.…”
mentioning
confidence: 99%
“…12−16 Among the characterization techniques employed, some rely on changes in size and surface charge during the formation of the PC including dynamic light scattering (DLS), 17 (FCS), 18−20 UV−visible spectroscopy, 21,22 and gel electrophoresis. 23,24 In addition, mass spectrometry (MS), 25,26 circular dichroism (CD), 27,28 and Fourier transform infrared spectroscopy (FT-IR) 29,30 enabled the identification and quantification of proteins in the corona. However, as most techniques are not in situ, they result in long processing times, molecular biases in purification processes, and loss of singleparticle information.…”
mentioning
confidence: 99%